Transformative Da’wah and Wasathiyah Islam: A Contextual Analysis of TGH. L. Muhammad Turmudzi Badaruddin’s Communicative Strategy: Dakwah Transformatif dan Islam Wasathiyah di Lombok: Analisis Kontekstual atas Strategi Komunikasi TGH. L. Muhammad Turmudzi Badaruddin” - Amri Malik Aziz Rahman (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2025)
This study examines the da’wah communication strategies of TGH. L. Muhammad Turmudzi Badaruddin in Lombok, Indonesia, a region facing religious polarization and growing challenges of intolerance. Using a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis at Pondok Pesantren Qamarul Huda Bagu. The findings reveal a multimodal da’wah approach that integrates bil-lisan (oral preaching), bil-hal (exemplary conduct), and bil-kitabah (written texts), institutionalized through pesantren-based education and community initiatives. These strategies not only foster tolerance and social cohesion but also embed wasathiyah Islam into local socio-economic structures such as pesantren cooperatives. Theoretically, this study extends da’wah communication theory by situating it within contemporary frameworks of mediatized and contextual religion, demonstrating how pesantren leadership functions as communicative authority in multicultural societies. Practically, the study highlights the potential of pesantren-based leaders to institutionalize Islamic moderation as a sustainable model for peacebuilding and civic engagement beyond individual charisma.